Controle social exercido através da denúncia no âmbito do TCE-RJ - Lemos, Carlos Eduardo Enriques Feio de (2008)
The crisis that affected the capitalist states during the last decade of the 20th century, put an end to the period of greatest expansion of the state, demanding alterations that brought, especially in economic terms, the ideals of the liberal state. The main goal of these changes was to optimize the administration of the public service by introducing into it more efficiency, transparency, and morality because the state had shown to be incapable of attending the demands of the society and its way of doing was inefficient and did not reach out to the public interest. In Brazil, like in other part of the world, recent scandals of corruption and misuse of public funds put in doubt the efficiency of the financial control system. Like any other political system Brazil has a complex set of external and internal control, institutions that work to prevent misuse of public funds and identify responsibilities if bad use occurred. All these elements highlight the mechanisms of control of the public administration, which came to be seen as essential instruments for the improvement of the management of the public resources, targeting the collective interest. Therefore, along with the traditional mechanisms of power suppression, such as the system of checks and balances, social control arises. This, when used together with the monitoring exercised by public inspection agencies, is defined as horizontal accountability activated by civil society, in which citizens and institutions gather efforts in order to promote a more effective charge of responsibility from public agents and politicians in case of misconducts. This study aimed to identify the opportunities and limitations of social control exercised by the complaint under the TCE-RJ. The results point to the need to develop measures to guarantee the anonymity of denouncers, to simplify the forms of access the TCE-RJ and to improve information spread to the citizen.